Visual Preference for Future Kuala Lumpur Riverfront: An Overview - Hilaluddin, Raudhah; Ujang, Norsidah (School of Social Sciences, 2015)
Rapid urbanization and population growth of Kuala Lumpur city have drastically changed the relationship between the society and the river. It is unfortunate that for years, the Klang and Gombak River has been transformed into a concrete drainage and lost its identity. This is worsened by the lack of aesthetic value and the absence of social activities along the riverside area. ‘River of Life’ (RoL) project initiated by the Kuala Lumpur City Hall is an ambitious attempt to revitalize the Kuala Lumpur riverfront. Since the proposed riverfront involves in making new public spaces for the community, the community preference for the visual image of the riverfront should be considered. This paper discusses the importance of visual preference and the influencing factors in recreating a successful riverfront. The finding is important to consider in designing Kuala Lumpur future riverfront that suits the character of the city and fulfill the community perceptions.